2020
DOI: 10.21203/rs.2.18641/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NT-4 attenuates neuroinflammation via TrkB/PI3K/FoxO1 pathway after germinal matrix hemorrhage in neonatal rats

Abstract: Background: Neuroinflammation plays an important role in pathogenesis of germinal matrix hemorrhage (GMH). Neurotrophin-4 (NT-4) is a member of the neurotrophin family, and it interacts with the tyrosine kinase B (TrkB) receptor. It has been studied that NT-4 has neuroprotective effects following cerebral ischemia. We aimed to investigate the neuroprotective function of NT-4 and it’s high affinity receptor TrkB as well as its downstream mediator phosphatidylinositol-3-kinases (PI3K)/protein kinase B (Akt)/Fork… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…For example, TrkB selectively binds BDNF and NT4 (reF. 19 ), and TrkC has a high affinity for NT3 (reF. 20 ).…”
Section: The Biology Of Ngfmentioning
confidence: 99%
“…For example, TrkB selectively binds BDNF and NT4 (reF. 19 ), and TrkC has a high affinity for NT3 (reF. 20 ).…”
Section: The Biology Of Ngfmentioning
confidence: 99%
“…In normal settings, AKT downregulates FoxO1 signaling by phosphorylation at three phosphorylation sites: Thr24, Ser256, and Ser319 (Zhang et al., 2018). During ischemia, phosphorylation of PI3K/Akt is inhibited causing decreased FoxO1 phosphorylation as well as increased nuclear translocation (He et al., 2019; Wang et al., 2020) and gluconeogenesis regulation (Pitaloka et al., 2019). Recent studies showed that mebhydrolin or puerarin ameliorated blood glucose homeostasis by suppressing hepatic gluconeogenesis via activation of the PI3K/AKT/FoxO1 pathway in T2DM mice (Liu et al., 2021; Zhao et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for Nissl staining was the same as in previous studies [25]. Brain slices (10 mm thick) were dehydrated in 95% and 70% FLEX (ThermoFisher) for 1 min respectively, then rinsed with tap water and distilled water for 10 s. The brain slices were then stained in 0.5% cresyl violet (Sigma-Aldrich) for 1.5 min, followed by rinsing with distilled water for 10 s, and then put into the dehydration in 100% FLEX and xylene for 1 min (twice each).…”
Section: Nissl Stainingmentioning
confidence: 99%